ANALISIS EFEKTIFITAS SISTEM PENERBITAN SURAT PENYEDIAAN DANA PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KABUPATEN MINAHASA - Nofry, Sampoel Johanes; Sondakh, Jullie J; Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
The Letter of Provision of Funds is the first step in the cash disbursement transactions for the Unit of Work Device Area within a region. The system contained in the process for issuing letters of Provision of Funds has been determined by the Minister of Home Affairs regulation number 21 year 2011. This study aims is to determine how the effectiveness of the system applied to the Regional Financial and Asset Management Agency of Minahasa District in issuing the Letter of Provision of Funds based on SE.903/316/BAKD. The result of the research shows that the Regional Financial and Asset Management Agency of Minahasa has been effective in issuing letter of provision of funds in accordance with the Regulation of the Minister of Home Affairs Number 21 Year 2011 SE.903/316/BAKD concerning guidelines on regional financial management.